1985
DOI: 10.1111/j.1752-1688.1985.tb00154.x
|View full text |Cite
|
Sign up to set email alerts
|

VALUATION OF IMPROVED IRRIGATION EFFICIENCY FROM AN EXHAUSTIBLE GROUNDWATER SOURCE1

Abstract: This paper presents estimates made via a recursive linear programming model of the net benefits of improving irrigation application efficiency from an exhaustible groundwater source. Net benefits were derived for different application efficiency levels under furrow, sprinkler, and LEPA irrigation systems. In addition, net benefit estimates were obtained for the transition across irrigation systems. Solutions from the model indicate that low crop prices have a differential impact on net benefits across irrigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1985
1985
2001
2001

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…An estimated 17,817,000 acre-feet of ground water was pumped in 1980 (Heimes and Luckey, 1983). Decline soon followed because of physical depletion of the aquifer, increasing energy prices, and lower crop prices (Lee et al, 1985). Together, lower water availability and higher energy prices define the economic depletion of the aquifer.…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 17,817,000 acre-feet of ground water was pumped in 1980 (Heimes and Luckey, 1983). Decline soon followed because of physical depletion of the aquifer, increasing energy prices, and lower crop prices (Lee et al, 1985). Together, lower water availability and higher energy prices define the economic depletion of the aquifer.…”
Section: Introductionmentioning
confidence: 99%
“…In a comparison of low energy precision application (LEPA), drip, sprinkler, and furrow irrigation systems under Texas conditions, Hall et al (1988) found that LEPA sprinkler irrigation systems were the most profitable. However, Lee et al (1985) found that converting from furrow T surface to LEPA center pivot sprinkler irrigation systems was less profitable than improving the application efficiency of existing furrow surface systems. The study focused on cost of production and investment impacts of alternative irrigation systems and application efficiencies, but did not account for potential effects upon irrigated crop yields.…”
mentioning
confidence: 99%
“…Previous studies have indicated that a strong trend exists among irrigated crop producers in the Great Plains region to convert to more efficient irrigation systems and to adopt more water-efficient cropping systems in response to declining groundwater supplies (Lacewell, 1998;National Research Council (NRC), 1996; Council for Agricultural Science and Technology (CAST), 1996; Lee et al, 1985). However, results vary in the Great Plains and other regions regarding which type of irrigation system is most profitable to use.…”
mentioning
confidence: 99%